EVALUASI PERAN PENDAMPING TERHADAP KEBERHASILAN PROGRAM DESA MANDIRI PANGAN DI KABUPATEN BANTUL - , NURUL AIDA LUTHFIANTI; , Prof. Dr. Ir. Sunarru Samsi Hariadi ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research was aimed to determine : (1) the roles of facilitators in Village Food Autonomy Program and (2) factors affecting the success of Village Food Autonomy Program. This research was conducted in two areas in Bantul regency: Karangtengah village, Imogiri subdistrict and Argodadi village, Sedayu sub-district. Analytical descriptive method by employing quantitative approach using survey was used in the research. Respondents were selected from the population under study by using simple random sampling. The total number of respondents were 60 people, consisting of 30 respondents from Karangtengah village and 30 respondents from Argodadi village. Data were analyzed by using proportion test, paired t â test, and multiple linear regression analysis. The research results showed that more than 50% of respondents evaluate that rated the role of facilitators in the Village Food Autonomy Program in Bantul in high category which meaned the supervisors has always played an active role in assisting and helping the community in the Village Food Autonomy Program. The major role of the program facilitators was as a motivator. This was equal to 73.81% of response from total respondents, which meaned the supervisors have been encouraging the community to achieve food autonomy in their village. Meanwhile, the least notable role of the facilitators was the role as an innovator, which was found in 44.88% of total response. That showed that the facilitators introduced their latest business innovation to the community in a very occasional manner only. Village officials was found to have a substantial role toward the success of Village Food Autonomy Program, which meaned as high as village officials as high as the success of Village Food Autonomy Program.The other factors that did not significantly affect the success of this